The Burden of Ventricular Premature Complex Is Associated With Cardiovascular Mortality - Lee, Po-Tseng; Huang, Ting-Chun; Huang, Mu-Hsiang; Hsu, Ling-Wei; Su, Pei-Fang; Liu, Yen-Wen; Hung, Meng-Hsuan; Liu, Ping-Yen (Frontiers in Cardiovascular Medicine, 2022)
Background: Ventricular premature complex (VPC) is one of the most common ventricular arrhythmias. Presence of VPC is associated with an increased risk of heart failure. Method: We designed a single-center, retrospective, and large population-based cohort to clarify the role of VPC burden in long-term prognosis in Taiwan. We analyzed the database from the National Cheng Kung University Hospital-Electronic Medical Record (NCKUH-EMR) and Holter (NCKUH-Holter). A total of 19527 patients who underwent 24-hour Holter electrocardiogram (ECG) monitoring due to palpitation, syncope, and clinical suspicion of arrhythmias were enrolled in the study. Results: Clinical outcome of interests involved 5.65% non-cardiovascular death and 1.53% cardiovascular-specific deaths between 2011 to 2018. Cox regression analysis, Fine and Gray’s competing risk model and propensity score matching demonstrated that both moderate (1000 – 10000/day) and high (> 10000/day) VPC burden contributed to cardiovascular death in comparison with low VPC burden (< 1000/day). Conclusion: A higher VPC burden via Holter ECG is an independent risk factor of cardiovascular mortality.